PENYULUHAN HUKUM PELANGGARAN PEMILIHAN KEPALA DAERAH SERENTAK TAHUN 2024 KEPADA MASYARAKAT UNTUK MEWUJUDKAN DEMOKRASI YANG BERMARTABAT - Munte, Herdi; Tommi, Missiniaki (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Legal counseling on violations of the 2024 Regional Head Election (Pilkada) plays a strategic role in realizing a dignified democracy. This study aims to analyze the importance of legal counseling in increasing public awareness of election violations, such as vote buying, abuse of power, and dissemination of misleading information. The research method used is normative legal research, with statutory and conceptual approaches. The results indicate that legal counseling is effective in empowering the community to actively monitor the election process, enhance political participation with integrity, and strengthen the legitimacy of election results. Comprehensive, continuous, and locally adaptive counseling enables the public to reject fraudulent practices and safeguard the integrity of democracy, ensuring that the 2024 Pilkada is conducted honestly, fairly, and with dignity.Keywords: Legal Counseling, Pilkada Violations, Dignified Democracy.